Production-Economc indicators of plum growing in teh Republic of Serbia - Kljajić, Nataša; Vuković, Predrag; Simonović, Zoran (Anali Ekonomskog fakulteta u Subotici, 2025)
The plum is highly represented in fruit growing, also has a high utility value, a significant participation in foreign trade exchange, and its production involves a fair amount of labor. It also contributes to the sustainable development of agriculture and ecology. The Republic of Serbia, with an average production of 441,420 t, ranks third in the world, and participates in world plum production with 3.86%. In the fruit growing of the Republic of Serbia, the plum is one of the dominant types of fruit. Average values ​​of areas under plum trees for the research period 2014-2023, were 37.44%. According to the average total production, plums are represented by 29.23% and are behind apples. However, plum production is accompanied by a relatively low yield (6.1 t/ha), which is below of the realistic possibilities if we take into account the favorable microclimatic and hydro-pedological features for plum production. With that in mind, some of the measures that should be taken in order to improve plum production and raise its production to the position it realistically belongs to have been proposed.